Pengaruh Perspektif Pembelajaran Pertumbuhan, Proses Bisnis Internal dan Keuangan pada Unit Layanan Terpadu Kementerian Kesehatan RI dengan Balanced Scorecard - Lukky jayadi (Kampurui Jurnal Kesehatan Masyarakat, 2020)
Growth learning perspectives, internal business processes and finance on the Integrated Services Unit Ministry of Health are used as benchmarks to determine the performance of services provided by using the Balanced Scorecard. This research is a descriptive qualitative research approach. Data collection techniques used are questionnaires and observation, while the methods of data analysis using descriptive analysis. Performance Integrated Services Unit Ministry of Health using a balanced scorecard approach assessed from the perspective of learning growth, internal business processes and finance obtained good results. From the above results are known Balanced Scorecard can be used as a performance measure in Integrated Services Unit Ministry of Health that mutually affect each performance perspective